Hyperspectral Multiplexed Biological Imaging of Nanoprobes Emitting in the Short-Wave Infrared Region - A. Yakovliev; R. Ziniuk; D. Wang; B. Xue; L. O. Vretik; O. A. Nikolaeva; M. Tan; G. Chen; Yu. L. Slominskii; J. Qu; T. Y. Ohulchanskyy (Nanoscale Research Letters, 2019)
Abstract Optical bioimaging with exogenous luminophores emitting in short-wave infrared spectral region (SWIR, ~ 1000–1700 nm) is a rapidly developing field, and the development of multiple SWIR-photoluminescent nanoprobes has recently been reported. In this regard, hyperspectral imaging (HSI), combined with unmixing algorithms, is a promising tool that can allow for efficient multiplexing of the SWIR-emitting nanoagents by their photoluminescence (PL) spectral profiles. The SWIR HSI technique reported here is developed to multiplex two types of nanoprobes: polymeric nanoparticles doped with organic dye (PNPs) and rare-earth doped fluoride nanoparticles (RENPs). Both types of nanoprobes exhibit PL in the same spectral range (~ 900–1200 nm), which hinders spectral separation of PL with optical filters and limits possibilities for their multiplexed imaging in biological tissues. By applying SWIR HSI, we exploited differences in the PL spectral profiles and achieved the spectrally selective and sensitive imaging of the PL signal from every type of nanoparticles. Unmixing of acquired data allowed for multiplexing of the spectrally overlapping nanoprobes by their PL profile. Both quantitative and spatial distribution for every type of nanoparticles were obtained from their mixed suspensions. Finally, the SWIR HSI technique with unmixing protocol was applied to in vivo imaging of mice subcutaneously injected with PNPs and RENPs. The applicability of hyperspectral techniques to multiplex nanoprobes in the in vivo imaging was successfully demonstrated.